Early Development of Two Neovascular Glaucoma Cases Following Central Retinal Artery Occlusion - Yıldırım, Hakan; Canleblebici, Mehmet; Balbaba, Mehmet; Çeliker, Ülkü (My University, 2019)
Central retinal artery occlusion (CRAO) is an ophthalmic emergency which causessudden loss of vision. One of its most serious complications is neovascular glaucoma (NVG), and frequently seen between mostly the second and third months after the diagnosis. In this study, 2 casesof immediately developing glaucoma after CRAO are presented and possible risk factors are discussed. Our first case who developed NVG within four weeks could not complete her treatment dueto myocardial infarct during hyperbaric oxygen treatment. On the other hand, our second case wasreferred to hyperbaric oxygen treatment but her treatment could not begin due to a gynecologicaldisease and she could not attend her regular follow-ups. When these two cases, having NVG withinfour week after CRAO are examined, it should be considered that early development NVG mayoccur immediately after CRAO as an additional disease, which may increase ischemia, in patientswho are incompatible and not attending follow-ups regularly.
Keywords: Genel ve Dahili Tıp; Patoloji; Göz Hastalıkları